Kinerja Masjid Berbasis Inovasi: Perspektif Indonesia - Danarahmanto, Pri Agung; Widana, IGN Oka (ITB AAS INDONESIA Surakarta, 2024)
Islam is the fastest growing religion in the world. With this growth, many new mosques have emerged, but they are not necessarily accompanied by good mosque performance. The purpose of this research is to provide an understanding of the relationship between mosque resources, innovation, and mosque performance in Indonesia. This study involved 100 respondents who regularly or have made repeat visits to the mosque. Respondents participated by completing questionnaires through online surveys. The data were analyzed using regression and path analysis. The results of this research indicate that innovation plays a crucial role in improving mosque performance. Innovation needs to be supported by the availability of resources in order to achieve good performance. Innovation has a greater influence compared to resources in enhancing mosque performance. The indirect effect of mosque resources on mosque performance through innovation is greater than the direct effect without going through innovation. Novelty is achieved by testing and analyzing the relationship between mosque resources, innovation, and mosque performance in one model, as well as revealing the important role of innovation as an intervening factor that affects the relationship between resources and mosque performance.